Um ensaio sobre a comunicação interna pós-industrial em sua dicotomia discurso e prática - Cabral, Valéria (Organicom, 2004)
We live a time in which the organizations, still under the aegis of a decaying mechanicist model, earnestly demand the development of up-to-date practices on the communication with their employees, in order to reach success in an enterprise environment marked by instability, strain and eagerness for more and more innovative and qualified products and services.